The Brainstem-Vermis and Brainstem-Tentorium Angles in the Fetus: A Study of Their Reproducibility by Fetal Magnetic Resonance Imaging and Their Evolution Along the Gestation - Prieto, Laura Joigneau; Ruiz, Yolanda; Pérez, Laura; Bravo, Coral; Aguado, Alejandra; Alvarez-Mon, Melchor; Ortega, Miguel A.; Marín, Carlos; De León-Luis, Juan (Frontiers in Medicine, 2022)
Aim: To assess the reproducibility of brainstem-vermis (BV) and brainstem-tentorium (BT) angles measured by fetal Magnetic Resonance Imaging (MRI) during second half of pregnancy in normal and abnormal fetuses. Secondly, to assess reproducibility of two alternative methodologies to measure the brainstem-tentorium angle (BT1 and BT2) proposed by our group that could be more reliable in fetuses with posterior fossa fluid collection (PFFC) anomalies. Finally, to describe the evolution of BV and BT angles along gestation in normal fetuses. , Methods: We conducted a cross-sectional study of BV and BT angles obtained by MRI performed at our center, in 22 fetuses with PFFC and 8 fetuses without PFFC to calculate both angles’ reproducibility and the correlation between them and the gestational age. Results: We found good interobserver reproducibility for the BV, BT1 and BT2 angles (Intraclass correlation coefficient: 0.98; 0.89 and 0.88 for each of these angles, with p<0.001). In patients with PFFC the BT angle could not always be measured. BT angle presented a positive relationship with gestational age (p=0.002) but BV angle stayed stable. The measurements of BV, BT1 and BT2 angles can be reliably performed by MRI with good interobserver reproducibility. , Conclusions: BV angle stays stable during pregnancy, whereas BT angle tends to augment with gestational age.